Redundancy Pay and Collective Dismissals - Laszlo Goerke (Center for Economic Studies and ifo Institute (CESifo), 2001)
Redundancy payments for collective dismissals are incorporated into a Shapiro-Stiglitz model of efficiency wages. It is shown that a fixed payment will lower wages, leave employment and welfare unaffected if there are no wage-dependent taxes, no additional firing costs and if unemployment benefits are not altered by redundancy payments. If payroll taxes exceed firing costs and unemployment benefits are independent of redundancy pay, employment and welfare will rise with redundancy payments. If these payments are also a function of previous wages, positive employment effects will be mitigated. A substitution of wage-dependent for lump-sum redundancy payments can lower employment, allowing for a continuous variation of effort.
Keywords: 330; collective dismissal; efficiency wages; employment; redundancy pay; welfare